Density-functional calculations for Ce, Th, and Pu metals and alloys - Landa, A.; Soderlind, P. (Condensed Matter Physics, 2004)
The phase diagrams of Ce, Th, and Pu metals have been studied by means
of density-functional theory (DFT). In addition to these metals, the phase
stability of Ce-Th and Pu-Am alloys has been also investigated from firstprinciples
calculations. Equation-of-state (EOS) for Ce, Th, and the Ce-Th
alloys has been calculated up to 1 Mbar pressure in good comparison to
experimental data. Present calculations show that the Ce-Th alloys adopt
a body-centered-tetragonal (bct) structure upon hydrostatic compression
which is in excellent agreement with measurements. The ambient pressure
phase diagram of Pu is shown to be very poorly described by traditional
DFT but rather well modelled when including magnetic interactions. In particular,
the anomalous δ phase of Pu is shown to be stabilized by magnetic
disorder at elevated temperatures. The Pu-Am system has also been studied
in a similar fashion and it is shown that this system, for about 25% Am
content, becomes antiferromagnetic below about 400 K which corroborates
the recent discovery of a Curie-Weiss behavior in this system. Фазові діаграми металів Ce, Th та Pu вивчаються за допомогою теорії функціоналу густини (ТФГ). Крім того, фазова стабільність сплавів Ce-Th та Pu-Am досліджена з першопринципних розрахунків. Рівняння стану для Ce, Th та сплаву Ce-Th було розраховано аж до тиску 1 Mбар в доброму узгодженні з експериментальними даними. Дані розрахунки показують, що сплави Ce-Th приймають об’ємоцентровано-тетрагональну структуру внаслідок гідростатичного стиску, що чудово узгоджується з вимірюваннями. Показано, що фазова діаграма Pu при нормальному тиску дуже погано описується традиційною ТФГ, але досить добре моделюється при включенні магнітних взаємодій. Зокрема показано, що аномальна δ -фаза Pu стабілізується магнітним безладом при підвищених температурах. Система Pu-Am також була досліджена подібним чином та показано, що ця система, при приблизно 25% вмісту Am, стає антиферомагнітною нижче приблизно 400 K, що узгоджується з недавнім відкриттям поведінки Кюрі-Вейса в цій системі.